Cuantificación de calcio, fosforo y hierro en la parte comestible de cynara scolymus l. “alcachofa” procedente del mercado La Hermelinda, Trujillo - Robles Gottfried, Basilia Anali (2011)
The concentration of calcium, phosphorus and iron in Scolimus Cynara "aalcachofa" by complexometric methods for Calcium, Fiske and Subbarrow Method for Phosphorus and Munsay colorimetric method with phenanthroline for iron was determinated. 35,84 mg% for calcium, 18,3 mg% phosphorus, and 0,88 mg% iron were found. The calcium and phosphorus values are lower than those reported in other studies. Iron values are consistent with those reported in other studies